2003
DOI: 10.1126/science.1085721
|View full text |Cite
|
Sign up to set email alerts
|

Active Nonmetallic Au and Pt Species on Ceria-Based Water-Gas Shift Catalysts

Abstract: Traditional analysis of reactions catalyzed by supported metals involves the structure of the metallic particles. However, we report here that for the class of nanostructured gold- or platinum-cerium oxide catalysts, which are active for the water-gas shift reaction, metal nanoparticles do not participate in the reaction. Nonmetallic gold or platinum species strongly associated with surface cerium-oxygen groups are responsible for the activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

73
2,236
7
20

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 2,807 publications
(2,381 citation statements)
references
References 18 publications
73
2,236
7
20
Order By: Relevance
“…1,2,3,4,5 The key point at the basis of its catalytic activity is the low energy cost for the formation of oxygen vacancies and Ce 3+ centers. Since these chemical species are extremely catalytically active, a huge amount of studies have focused on the strategies to maximize their amount, stability and organization.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,3,4,5 The key point at the basis of its catalytic activity is the low energy cost for the formation of oxygen vacancies and Ce 3+ centers. Since these chemical species are extremely catalytically active, a huge amount of studies have focused on the strategies to maximize their amount, stability and organization.…”
Section: Introductionmentioning
confidence: 99%
“…6 The formation of the Pt 5 Ce alloy was also detected by Bernal et al for Pt/CeO 2 samples reduced at 1173 K. 7 The hypothesis that the real catalytic site results from the interaction of platinum with the support surface found experimental evidence in the work of Fu et al, who observed that Pt supported on ceria continued to be active for the water gas-shift reaction also after leaching the metal phase by CN -and concluded that the catalytic sites are constituted by Pt 2+ and Pt 4+ species atomically dispersed in the oxide matrix. 10 The possibility that some kind of strong metal-support interaction (SMSI) is operative in TWCs and affects the catalytic properties was put forth by different authors, 2,3,[11][12][13] although there is not a general agreement about the beneficial or detrimental effect of such an interaction. Aiming at a structural characterization of the metal-support interface, we carried out in situ XAS experiments on the Pt L III edge of a Pt/ceria-zirconia catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Cerium oxide (CeO 2 ) is a semiconductor with wide band gap energy (3.19eV). In the recent years, much effort has been made towards the development of new synthetic routes for preparing nanostructure cerium oxides due to their potential uses in many applications, such as high-storage capacitor devices, buffer layers for conductors, fuel cells, polishing materials, UV blocks and optical devices [1][2][3][4][5][6][7] . The cerium oxide nanoparticles are prepared by various methods [8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%